Implementation of Al-Qur'an Learning Methods at Madrasah Aliyah Al-Masfuriyah - Almaydza Pratama; Abdul Azis (Institut Agama Islam Negeri Kerinci, 2023)
Learning is a process carried out by teachers in guiding their students to have learning experiences in achieving teaching goals, both in learning the Al-Qur'an itself. The aim of this research is to describe the implementation of Al-Qur'an learning at Madrasah Aliyah al Masfuriah. This research method is qualitative, namely field research. The results of the research are the application of the Tilawah method in studying the Al-Qur'an at Madrasah Aliyah Al-Mafuriyah following the rules that have been implemented by the institution. The application of the Tilawah method is carried out through several activity strategies, namely opening, core and closing activities. The opening activity begins with both reading Surah Al-Fatiha and reading Asamul Husna, the next agenda is the core activity which uses the classical method, and the last is the closing activity which ends with evaluating each student and closing with prayer.